2017
DOI: 10.1542/peds.2016-1159g
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Fragile X Syndrome Newborn Screening Landscape

Abstract: Background Fragile X syndrome (FXS) is the most common known inherited form of intellectual disability. Early identification is an important step in linking FXS individuals with appropriate and timely medical and social services. Newborn screening (NBS) is 1 approach that has been used for other conditions to facilitate early identification. Methods A literature review was conducted to identify issues, barriers, challenges, and approaches to addressing challenges related to NBS for FXS. Search terms included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Because adequate mitochondrial function is essential for synaptic protein translation during plasticity, synaptogenesis may represent, on the one hand, a critical period of vulnerability for FMRP deficient neurons and, on the other hand, a window for therapeutic intervention 6 . Synaptogenesis in the human brain peaks within the first 2 years of life, however, treatment strategies for infants with FXS currently do not exist 83,84 . This is largely because children do not present with signs and symptoms of FXS until about 3‐4 years of life 85 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because adequate mitochondrial function is essential for synaptic protein translation during plasticity, synaptogenesis may represent, on the one hand, a critical period of vulnerability for FMRP deficient neurons and, on the other hand, a window for therapeutic intervention 6 . Synaptogenesis in the human brain peaks within the first 2 years of life, however, treatment strategies for infants with FXS currently do not exist 83,84 . This is largely because children do not present with signs and symptoms of FXS until about 3‐4 years of life 85 .…”
Section: Discussionmentioning
confidence: 99%
“…This is largely because children do not present with signs and symptoms of FXS until about 3‐4 years of life 85 . Although there has been a push for the institution of prenatal or newborn screening for the disease, the lack of targeted and effective therapy for infants has served as a major barrier 84 . Thus, development of effective treatments for infants and young children with FXS, such as CoQ 10 , could bolster the case for newborn screening.…”
Section: Discussionmentioning
confidence: 99%
“…More detail on potential research that could provide the evidence needed to assess the feasibility and utility of newborn screening for FXS can be found in a companion article by Riley and Wheeler in this supplement. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The availability of screening will increase earlier identification of individuals at high risk for developmental delay and intellectual disability, as well as avoiding a diagnostic odyssey, as explained in some recent studies. (15)(16)(17) The screening approach using an ID kit removes the need for additional CE with non-expanded samples, hence providing cost savings. The combined approach for this study demonstrated that conservatively, only < 15% of samples needed to be characterised using the conventional method, resulting in cost savings of at least 30%.…”
Section: Page 10 Of 16mentioning
confidence: 99%